(untitled) (Research, Society and Development, 2021)
Reinforced concrete consists of a material susceptible to attack by pathological manifestations caused by the flow of aggressive agents in its porous environment, which damage its steel armor, reduce the level of resistivity of its mechanical properties and generate irreversible damage to the structure when none intervention is carried out opportunely. Thanks to this, predictive mathematical models must be used as a preventive measure in order to contribute to the reduction of socioeconomic impacts caused by the interdiction of these structures to carry out corrective maintenance and to the reduction of the environmental impacts that are caused when a large-sized structure collapses. Thus, this research will present the most current predictive mathematical models in the international literature, through bibliographic review, which can be used to prevent damage caused by carbonation and by attack by chloride ions. Among the results found, the possibility of using mathematical models in the prediction of the aforementioned pathological manifestations is highlighted with the use of partial differential equations whose solutions can be obtained with the aid of computational software, beyond your contribution to the prevention of damage evolution promoted by the pathologies in question so that they do not reach a level where maintenance costs are higher, making it possible to carry out preventive maintenance at appropriate times in order to prolong the useful life of the structure.